Seamount attractiveness to top predators in the southern Tyrrhenian Sea (central Mediterranean). (28th October 2015) - Fiori, C.; Paoli, C.; Alessi, J.; Mandich, A.; Vassallo, P.
Abstract : Seamounts are expected to attract pelagic top predators due to the higher abundance of possible prey aggregating around these structures. The importance of seamounts on benthic fauna and bottom fish is vastly documented, while little is known about their role as possible hotspots of pelagic biodiversity. This aspect is poorly investigated in the Mediterranean Sea, a basin considered a hotspot of endemism and biodiversity where, in addition, seamounts are widely present, with 227 structures. Our study focuses on the determination of the attraction effect of seamounts on some pelagic species in a Mediterranean sub-basin: the Tyrrhenian Sea. Here, seamounts are thought to be attraction structures for pelagic top predators. Cetaceans and sea turtles were found to be the most attracted taxa among the top predators taken into consideration with peak of presence around 5–10 miles from the seamounts.